2019
DOI: 10.2174/1389450120666181204165344
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 2 in Cellular Senescence and Cancer. A Structural and Functional Review

Abstract: <P>Background: Cyclin-dependent kinase 2 (CDK2) has been studied due to its role in the cell-cycle progression. The elucidation of the CDK2 structure paved the way to investigate the molecular basis for inhibition of this enzyme, with the coordinated efforts combining crystallography with functional studies. </P><P> Objective: Our goal here is to review recent functional and structural studies directed to understanding the role of CDK2 in cancer and senescence. </P><P> Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Cancer cells frequently show a gain of proliferation, cell cycle aberrations, loss of genomic and chromosomal stabilities, and metabolic alterations. , More than 80% of the cellular pathways such as cell cycle progression, transcription, DNA repair, and metabolic events are regulated by protein kinases through phosphorylation/dephosphorylation. Out of different protein kinases, overexpression of cyclin-dependent kinases (CDKs) (EC 2.7.11.22) is associated with the majority of cancer types, and thus, identification and establishment of CDKs targeted inhibitors become an attractive approach for cancer therapy. …”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells frequently show a gain of proliferation, cell cycle aberrations, loss of genomic and chromosomal stabilities, and metabolic alterations. , More than 80% of the cellular pathways such as cell cycle progression, transcription, DNA repair, and metabolic events are regulated by protein kinases through phosphorylation/dephosphorylation. Out of different protein kinases, overexpression of cyclin-dependent kinases (CDKs) (EC 2.7.11.22) is associated with the majority of cancer types, and thus, identification and establishment of CDKs targeted inhibitors become an attractive approach for cancer therapy. …”
Section: Introductionmentioning
confidence: 99%
“…CDK2 is a Ser/Thr protein kinase that plays a crucial role in timely regulating cell cycle progression, and its dysregulation in human cancers usually contributes to uncontrolled tumor proliferation. , Therefore, CDK2 is regarded as a pivotal pharmacological target for developing anticancer therapies and is extensively investigated in recent docking and MD simulation studies. ,,, These studies on CDK2 have revealed significant conformational flexibilities of the ATP-binding pocket, a site located at the interface of two subdomains. Here, we apply the iterANM method, which has been reported to explore the conformational space of domain movements efficiently, to generate the ensemble of apo CDK2 and evaluate its role in improving the prediction accuracy of molecular docking.…”
Section: Resultsmentioning
confidence: 99%
“…This electrophile‐sensitive (ES) strategy has previously been successfully applied to c‐Src, Aurora A and EphB1 kinases by using established adenosine mimetics as starting scaffolds [21,22] . Here, we looked to apply the ES strategy to study cyclin‐dependent kinase 2 (Cdk2), which is a clinically important serine/threonine kinase in oncology, its activity is important for driving cell replication and is dependent upon association with a cyclin protein [23] . The high degree of active‐site homology within the Cdk family, has meant that developing Cdk2‐specific inhibitors has proved elusive and, as such, selective inhibitors of electrophile sensitive Cdk2 would be highly valuable tools [24] …”
Section: Figurementioning
confidence: 99%
“…[21,22] Here, we looked to apply the ES strategy to study cyclin-dependent kinase 2 (Cdk2), which is a clinically important serine/threonine kinase in oncology, its activity is important for driving cell replication and is dependent upon association with a cyclin protein. [23] The high degree of active-site homology within the Cdk family, has meant that developing Cdk2-specific inhibitors has proved elusive and, as such, selective inhibitors of electrophile sensitive Cdk2 would be highly valuable tools. [24] To generate an ES Cdk2 construct (Cdk2(ES)), we mutated the gatekeeper phenylalanine residue to cysteine (F80 C) to enable covalent binding in the active site.…”
mentioning
confidence: 99%